Notes on the Ancient Population from the Area of Dilunto (A Few Examples from the South of the Province Dalmatia) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The paper presents data on the population from the south of the province Dalmatia (Dilunto / Stolac). The conquest of the Illyrians and the education in the province of Dalmatia led not only to territorial but to ethnic changes as well. As shown by the epigraph statues from the valley of the Bregava (Dilunto / Stolac), the locals, during the Roman rule, lived together with the Romans who came to the area (cives Romani). A stronger influence of the Roman culture and civilisation, as well as lifestyle, was mostly pronounced by the Italic peoples, as highly significant contributors. They brought with themselves all the achievements of the Roman civilisation, which influenced the locals in various ways. Epigraph statues, various archeological findings and oral sources shed light to a certain degree on all these facts in the south of the province Dalmatia.
Keywords: the province Dalmatia; Dilunto / Stolac; epigraph statues; local population; the Italic peoples